IMPLEMENTASI HAK PEKERJA DALAM HAL UPAH DI KANTOR NOTARIS - Diah Aju Wisnuwardhani (University of Merdeka Malang, 2017)
Traffic law, almost all legal acts require legal guarantees for such actions. One of the legal guarantees is an authentic deed made by a Notary. The Notary attributively has the authority to make authentic deeds, to ratify deeds under the hand as well as to some other authorities regulated by the Notary Law. Implementation of such authority, the notary requires employees (workers) to serve and expedite services provided to the parties or clients of the notary. As workers, notary employees are entitled to wages and other rights as workers as stipulated in the Manpower Act. On the one hand, a notary public, a notary as well as an employer who is obliged to perform wages and other rights of workers as stipulated in the Manpower Act. Working relationships conducted by workers and employers are generally subordinate in nature. The position of the workers in the employment relationship, in terms of economic social is lower than the employer, for the workers need a container to reach the point kesedarajatan with employers. The most prominent civil and political rights needed by every worker is the right to peaceful assembly and assembly.